PHYSICAL AND CHEMICAL QUALITY CHARACTERISTICS OF CORN TORTILLAS WITH SUBSTITUTE PURPLE SWEET POTATO FLOUR - Nurfitrianti Bulotio; Adnan Engelen; Nursia Lateka (UPPM Politeknik Gorontalo, 2021)
This study aimed to test the physical and chemical quality characteristics of corn tortillas with substitute purple sweet potato flour. This study used a completely randomized design (CRD) and LSD test if there was a significant effect. The tests carried out included organoleptic tests, air content analysis, ash content analysis, color analysis and texture analysis. The results showed that the best formulation of tortillas chips was a P4 treatment with the addition of 75% purple sweet potato flour: 25% corn, with a texture value of 4.267, taste 4.75 and aroma 4.56 and for the best color treatment found in the addition of P3 had a value of 4.31. The best treatment in the chemical analysis is the P4 treatment had a color value of -10.93, moisture content of 8.94 and ash content of 2.57. For texture analysis test the highest treatment was P2 treatment with the addition of 25% purple sweet potato flour: 75% corn with a value of 1139.15.